THE COMPOTITION OF LONG LINE CATCHES IN THE MORNING AND IN THE AFTERNOON AT FISH AGGREGATING DEVICE (FAD) IN NORTH RUPAT RHU, BENGKALIS DISTRICT, RIAU PROVINCE. - Muhammad Zikri; Pareng Rengi; Bustari ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTmuhammadzikri191@yahoo.co.idThis research was conducted on 18th to 27th September 2014 in the waters of Rhu Bay Village, North Rupat District, Bengkalis, Riau Province. The purpose oh this research was to determine the longline catches (kg), the type and amount of catches in the morning and afternoon in the Fish Aggregating Device (FADs) in the waters of Bay Village, North Rupat Rhu, Bengkalis District, Riau Province. The method that is used in this research was a survey method, which is taking the catch area Fish Aggregating Device in the morning and evening for 10 days. The catches during the research were 14.8 kg (35 fishes). The types of longline catches of the highest and the lowest in the morning and afternoon of the fish aggregating Device as a whole is composed of fish species Polynemus tectraductylus was 6.84 Kg (17 fishes) which is the highest number of catches, Chirocentrus Dorab was 4.87 Kg (7 animals), Arius sp was 1.62 Kg (4 fishes), Diodon holocanthus was 0.72 Kg (4 fishes), and the lowest longline catches Pristigasteride was 0.75 kg (3 fishes). From the Ttest showed that the entire weight of longline catches in the morning and afternoon showed Thit value = 3.41, while Ttab = 2.22814, it is means that H0 is rejected. This is means that there are differences in longline catches the morning and afternoon Fish Aggregating Device. From the calculation of Ttest showed that there is no differences composition of longline catches in the morning and afternoon at Fish Aggregating Device.Keywords : Catches compotition, in the morning-in the afternoon, longline, fishaggregating device.